Avoidable Mortality Differences between Rural and Urban Residents During 2004-2011: A Case Study in Iran - Habib Omranikhoo; Abolghasem Pourreza; Hassan Eftekhar Ardebili; Hassan Heydari; Abbas Rahimi Foroushani (Kerman University of Medical Sciences, 2013)
BackgroundAvoidable mortality as an indicator for assessing the health system performance has caught the attention of researchers for a long time. In this study we aimed to compare the health system performance using this indicator in rural and urban areas of one of Iran's southern provinces. MethodsAll deaths (29916) which happened during 2004-2011 in Bushehr province were assessed. Nolte and McKee's avoidable deaths model was used to distinguish avoidable and unavoidable conditions. Accordingly, all deaths were classified into four categories including three avoidable death categories and one unavoidable death category. STATA software was used to conduct Poisson Regression Test and age-standardized death rate. ResultsFindings showed that avoidable mortality rates declined in both urban and rural areas at 3.33% per year, but decline rates were influenced by Ischemic Heart Disease (IHD) and preventable death categories to treatable death category. Annual decline rate for IHD category in rural and urban areas was nearly the same as 8%, but in preventable death category, rural areas experienced more decreases than urban ones (7% vs 5% respectively). However, decline rate in treatable mortality neither in urban and nor in rural areas was statistically significant. ConclusionDespite the annual decline in the rate of avoidable deaths, policy making initiatives especially screening and inter-sectoral measures targeting cause of deaths such as colon and breast cancers, hypertension, lung cancer and traffic accidents, can still further decrease avoidable deaths in both areas.